A new in vitro bioassay for cyst formation by renal cells from an autosomal dominant rat model of polycystic kidney disease - Pey, Roxana; Bach, Jürgen; Schieren, Gisela; Gretz, Norbert; Hafner, Mathias (In vitro cellular & developmental biology. Animal, 1999)
Autosomal dominant polycystic kidney disease (ADPKD) is one of the most frequent human inherited diseases. The main feature of the disease is the development of renal cysts, first occurring in the proximal tubules, and with time, dominating all segments of the nephron, leading to end-stage renal disease in 50% of the patients in their fifth decade of life. A therapy for polycystic kidney disease (PKD) has not yet been developed. Patients coming to end-stage ADPKD require long-term dialysis and/or transplantation. A suitable animal model to study ADPKD is the spontaneously mutated Han:SPRD (cy/ +) rat, but a method to cultivate Han:SPRD (cy/ +) derived renal cells which preserves their ability to form cyst-like structures in vitro has previously not been reported. Based on this well-characterized animal model, we developed a cell culture model of renal cyst formation in vitro. When renal cells of the Han:SPRD (cy/ +) rat were isolated and cultured under conditions that prevent cell-substratum adhesion, large amounts of cyst-like structures were formed de novo from Han:SPRD (cy/ +) derived renal cells, but only a few from control rat renal cells. In contrast, when cultivated on plastic as monolayer cultures, Han:SPRD (cy/ +)-derived and control rat-derived renal cells were indistinguishable and did not form cyst-like structures. Immunohistochemical characterization of the cyst-like structures suggests tubular epithelial origin of the cyst-forming cells. The amount of cysts formed from Han:SPRD (cy/ +)-derived renal cells grown in a stationary suspension culture is susceptible to modulation by different conditions. Human cyst fluid and epidermal growth factor both stimulated the formation of cysts from Han:SPRD (cy/ +)-derived renal cells whereas taxol inhibited cystogenesis. In contrast, neither human cyst fluid nor epidermal growth factor affected the amount of cysts formed by control rat renal cells. As the culture model reported here allows not only the distinction of PKD-derived tubular epithelium from its normal counterpart, but also the modulation of cyst formation especially by Han:SPRD (cy/ +)-derived renal cells, it might be a useful prescreening protocol for potential treatments for PKD and thus reduce the need for animal experiments.
Gesehen am 09.06.2022